2008
DOI: 10.1111/j.1537-2995.2008.01650.x
|View full text |Cite
|
Sign up to set email alerts
|

Improved postthaw viability and in vitro functionality of peripheral blood hematopoietic progenitor cells after cryopreservation with a theoretically optimized freezing curve

Abstract: Our results indicate that the current cryopreservation method for PBSCTs can be improved by either lowering the DMSO concentration to 5 percent or by using the theoretically optimized freezing curve. Infusion of less DMSO and more viable cells might improve the outcome of PBSCT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…The use of cryopreserved CB-derived CD34+ HSC is successful in children and usually leads to rapid hematopoietic recovery [2][3][4][5]. However, there is clearly room for improvements as current methods for ex vivo expansion of HSPC still result in a loss of multilineage differentiation potential and current freeze-thawing protocols result in significant cell death and loss of CD34+ HSPC populations essential for engraftment [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 97%
“…The use of cryopreserved CB-derived CD34+ HSC is successful in children and usually leads to rapid hematopoietic recovery [2][3][4][5]. However, there is clearly room for improvements as current methods for ex vivo expansion of HSPC still result in a loss of multilineage differentiation potential and current freeze-thawing protocols result in significant cell death and loss of CD34+ HSPC populations essential for engraftment [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 97%
“…HPC freezing can be performed at an uncontrolled rate,11,23‐25 at a controlled rate of approximately 1°C/min, or at tailored rates . The controlled‐rate protocol was reported in some studies as more efficient, enabling better colony‐forming unit recovery from frozen samples . Freezing curves, however, may rarely happen to be suboptimal: such an event may impair HPC vitality after storage and thus can be considered a major issue.…”
Section: Resultsmentioning
confidence: 99%
“…Differences regard many factors that have been demonstrated to affect the quality of the hematopoietic stem/progenitor cells after thawing. These are as follows: cell storage conditions before cryopreservation , cooling rate of cells (freezing curve) , temperature and speed of adding cryoprotective mixture and final DMSO and cell concentration . In particular, in our previous studies, we demonstrated that cryopreservation with 7·5% DMSO was associated with higher clonogenic potential and faster post‐transplant engraftment compared with 10% DMSO .…”
Section: Discussionmentioning
confidence: 99%
“…Many factors related to cryopreservation process of harvested PBPCs can affect their post‐thaw quality. Cell storage conditions before and after cryopreservation (liquid nitrogen vapour or mechanical freezer), concentration, cryoprotectants, freezing procedure, all have to be taken into account to ensure adequate quality of cryopreserved PBPCs including also HSCs from other sources like umbilical cord blood (UCB) or bone marrow (BM) .…”
Section: Introductionmentioning
confidence: 99%